mosGILT controls innate immunity and germ cell development in Anopheles gambiae - Gunjan Arora; Xiaotian Tang; Yingjun Cui; Jing Yang; Yu-Min Chuang; Jayadev Joshi; Andaleeb Sajid; Yuemei Dong; Peter Cresswell; George Dimopoulos; Erol Fikrig (BMC Genomics, 2024)
Abstract Gene-edited mosquitoes lacking a gamma-interferon-inducible lysosomal thiol reductase-like protein, namely (mosGILT null ) have lower Plasmodium infection, which is linked to impaired ovarian development and immune activation. The transcriptome of mosGILT null Anopheles gambiae was therefore compared to wild type (WT) mosquitoes by RNA-sequencing to delineate mosGILT-dependent pathways. Compared to WT mosquitoes, mosGILT null A. gambiae demonstrated altered expression of genes related to oogenesis, 20-hydroxyecdysone synthesis, as well as immune-related genes. Serendipitously, the zero population growth gene, zpg, an essential regulator of germ cell development was found to be one of the most downregulated genes in mosGILT null mosquitoes. These results provide a crucial missing link between two previous studies on the role of zpg and mosGILT in ovarian development. This study further demonstrates that mosGILT has the potential to serve as a target for the biological control of mosquito vectors and to influence the Plasmodium life cycle within the vector.